Synthesis, Application and Prospects of Carbon Dots as A Medicine Food Homology - Siqi Huang; Huili Ren; Hongyue Chen; Nuan Wen; Libo Du; Chaoyu Song; Yuguang Lv (Nanomaterials, 2025)
Against the background of the vigorous development of materials science and the deep cross-infiltration in many fields, a new medicine food homology, carbon dots (herein combined and abbreviated as MFH-CDs), has sprung up, showing great potential. This review used ChatGPT 4.0 to collect background information related to carbon dots, focusing on the common rich medicinal and food resources such as Lycium barbarum, Chinese yam, honeysuckle, and Ganoderma lucidum. These carbon dots are synthesized by hydrothermal synthesis, microwave radiation, and pyrolysis, which have the advantages of small particle size, high quantum yield, and low cytotoxicity. Recent studies have found that MFH-CDs have great application potential in biosensors, biological imaging, and drug delivery. In this paper, the characteristics of preparing carbon dots from different medicinal and edible resources and their applications in biology in recent years are reviewed, which provides in-depth guidance for the research and application of carbon dots from medicinal and edible biomass, helps it shine in multidisciplinary fields, and opens a brand-new journey from traditional medicinal and edible culture to cutting-edge technology application.